Birth outcomes in Flint in the early stages of the water crisis. Issue 1 (February 2018) - Abouk, Rahi; Adams, Scott
Abstract Following Flint's switching from the Detroit Water Authority to the Flint River as the source of its tap water, we show, using birth records, that there were lower average birthweights and higher incidence of low birthweight (< 2500 g) among infants. We compare these observed reductions in Flint birthweights to a series of counterfactuals. We find that among white mothers, there was a 71 g reduction in birthweight and a 26% increase in the incidence of low birthweight relative to what would have likely occurred without the water change. For infants of black mothers, we were unable to verify that the smaller reduction in birthweight was statistically different than what would have occurred without the water change. We consider lead contamination and stress as potential causes of the poor birth outcomes, as well as the reasons for the null effect among the infants of black mothers.